The Wilderness Solo Experience: A Unique Practice of Silence and Solitude for Personal Growth - Naor, Lia; Mayseless, Ofra (Frontiers in Psychology, 2020)
Silence is now acknowledged by science as a significant construct of healthy human development and well-being, linked to humans’ neurobiology, psychology, physiology, and spirituality. This paper focuses on a particular form of silence experienced through the solo experience in the wilderness. The solo experience, involving varying periods of time spent in solitude and silence in the wilderness is a common method of intervention implemented among therapeutic and educational nature-based approaches. Numerous studies and personal accounts in the field underscore the solo experience as one of the most significant nature based interventions linked to various beneficial outcomes. These studies emphasize the significance of the wilderness, far from daily demands, and devoid of technological stimuli allowing the silence, time and space for self-reflection and contemplation on the sacredness and meaning of life. Although new to modern culture, solitude in nature is an ancient form of initiation used ceremonially by indigenous cultures worldwide. These practices challenge the individual who alone in the wilderness battles fear and loneliness only to discover inner strengths and true identity. The solo experience, viewed as enacting these ancient rituals in modern form may serve as an antidote to the loneliness, stress, and depression on the rise in the current era, which have been linked to our overly stimulated urban environments and lifestyles. This paper sheds light on how the wilderness solo is experienced and understood, specifically as contributing to therapeutic outcome and personal growth. The empirical and theoretical literature is reviewed pointing to the significance of solitude and silence as basic components of the wilderness solo. These are linked to profound personal outcomes including the discovery of new and expansive ways of knowing the self and the world, specifically as interconnected in the larger web of life, enhancing a sense of personal belonging and purpose.